THE NEW RESPONDS TOWARD THE CHALLENGE: ISLAMIC DA'WAH AND CATHOLIC MISSION IN SEMARANG, 1890s-1940s - Mukhamad Shokheh (Paramita: Historical Studies Journal)
This study discusses the growth and development of religious movements and their effects on social life of religious communities during the period 1890s-1940s Semarang. The main problems of this study are the growth and development of Islamic dawah and Catholic mission and its influence on socio-religious life to the people in Semarang. This study used the historical method in order to answer the problem. The development of Islamic da'wah and Catholic missions in Semarang in the period 1890s-1940s could be seen into two mainstream, namely the renewal of dawah and indigenization of mission. Islamic da'wah and Catholic mission have brought progress to the social religious life of societies. Poeple in Semarang recognized the religious organization and new forms of leadership which more rational and democratic, and the growth of new awareness of identity from people to the identity as citizens.